Examining the Impact of Access and Encouragement on Consumption in an Elementary School Vegetable Snack Program - Bodnar, Josh; Chmielowska, Isabel; Fogarty, Jared; Martell, Kjirstin; Park, Shinhoo; Pergolski, Matthew; Scheller, Selena; Soborowicz, Levi; Jamelske, Eric M. (My University, 2018)
Given our study design explained on the previous poster, we now present results of our analyses. This poster provides both graphical and statistical comparisons of vegetable consumption across intervention conditions (no encouragement, moderate encouragement, high encouragement). Our primary outcome measure is proportion consumed calculated as (pre – post weight)/(pre – cup weight). This process yielded a continuous intake measure ranging from 0.00 to 1.00 for each student for each day that each vegetable was served. Independent samples t-tests were conducted to assess differences in student consumption across encouragement intervention conditions. Consumption differences within encouragement conditions were also analyzed over time using paired samples t-tests.
Color poster with text, charts, tables and graphs.
Keywords: Vegetables; Nutrition; Schoolchildren; Posters